2017
DOI: 10.18632/oncotarget.17413
|View full text |Cite
|
Sign up to set email alerts
|

The lymph node ratio as an independent prognostic factor for node-positive triple-negative breast cancer

Abstract: BackgroundWe aimed to evaluate the prognostic value of the lymph node ratio (LNR) in patients with axillary lymph node-positive triple-negative breast cancer (TNBC).MethodsThe prognostic efficacy was investigated in the first cohort from the Surveillance, Epidemiology, and End Results (SEER) dataset (n=4114) and was further validated in an independent cohort from Fudan University Shanghai Cancer Center (n=417). Patients were classified into low-, medium- and high-risk LNR groups.ResultsMultivariate analysis re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 27 publications
4
12
0
Order By: Relevance
“…It revealed that the LNR was an independent predictor of OS in high-risk patients. Considering the heterogeneity of TNBC, the LNR exhibits potential as an additional prognostic factor for TNBC patients with positive lymph node involvement [11]. In our study, we have also found that higher clinical N-stage is associated with increased ORs of distant metastasis.…”
Section: Discussionsupporting
confidence: 73%
“…It revealed that the LNR was an independent predictor of OS in high-risk patients. Considering the heterogeneity of TNBC, the LNR exhibits potential as an additional prognostic factor for TNBC patients with positive lymph node involvement [11]. In our study, we have also found that higher clinical N-stage is associated with increased ORs of distant metastasis.…”
Section: Discussionsupporting
confidence: 73%
“…A recent study had proposed the prognostic significance of the mLNR with TNBC patients. [10] To the best of our knowledge, our work is the largest study demonstrating the prognosis prediction of mLNR and grading in breast cancer patients with different molecular subtypes. Moreover, we found that the G-R staging system could identify the prognosis of breast cancer patients in Luminal and TNBC subtypes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[5–7] Till now, no consensus has been reached on the robust and reproducible classification of metastatic lymph node ratio (mLNR), [8] and limited studies revealing the prognostic value of mLNR in breast cancer patients with different molecular subtypes have been reported. [9,10]…”
Section: Introductionmentioning
confidence: 99%
“…They are characterized by higher invasiveness, heterogeneity, and a relatively poorer outcome than other subtypes (2)(3)(4). The clinical outcome of TNBC is associated with age at diagnosis, race, tumor size, histological grade, lymph node status, and the BRCA1 mutation as reported in many studies (1,5,6). Unlike other subtypes of breast cancer that receive treatments, such as endocrine therapy or trastuzumab, the main and only current systemic treatment option for patients with TNBC is chemotherapy (2).…”
Section: Introductionmentioning
confidence: 99%